Kajian Hukum Terhadap Anak Berhadapan Hukum Dalam Tindak Pidana Pencurian Menurut Undang-Undang No. 11 Tahun 2012 Tentang Pengadilan Anak (Studi Putusan No. 67/Pid.Sus-Anak/2017/PN. Mdn) - Muhammad Syahputra Lubis; Sri Hidayani; Muazzul Muazzul (JUNCTO: Jurnal Ilmiah Hukum, 2019)
In the Indonesian constitution, children have a strategic role that is explicitly stated that the state guarantees the right of every child to survival, growth and development and to protect against violence and discrimination. This type of research is normative juridical and is analytical descriptive in nature. The legal consequences of criminal acts of theft committed by children are reviewed in Law No. 11 of 2012 is a two-year prison sentence because a child offender is proven to have committed the crime of theft by force. Judge's considerations on Decision No. 67 / Pid.Sus-Anak / 2017 / PN.Mdn in terms of imposing penalties on perpetrators of theft perpetrated by children is that the acts committed have fulfilled the elements in the indictment namely Article 365 paragraph 1 to 1e and to the Criminal Code , and considering incriminating matters, namely the perpetrators' actions which disturb the community and harming the victims, and consider mitigating matters, namely the defendant being polite and has never been convicted